2020
DOI: 10.1007/s43076-020-00050-2
|View full text |Cite
|
Sign up to set email alerts
|

Selfies, Individual Traits, and Gender: Decoding the Relationship

Abstract: In the present scenario, no event whether formal or informal is complete without clicking a selfie. Selfies are especially in trend among young people, and they go can go to any extent often risking their lives for a perfect selfie. The hype is so much that even the mobile companies advertise their new handsets on the basis of selfie camera. Previous empirical studies found that typical selfie sufferers were those who intend to seek attention and habitually low in self-confidence, and they believe that posting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…A "Selfie" is a self-portrait snapshot taken with a smartphone held in hand or supported by a selfie stick and posted on social media platforms like Facebook, Instagram, and Snapchat (Richa et al, 2021). Oxford Dictionaries declared it the word of the year for 2013.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…A "Selfie" is a self-portrait snapshot taken with a smartphone held in hand or supported by a selfie stick and posted on social media platforms like Facebook, Instagram, and Snapchat (Richa et al, 2021). Oxford Dictionaries declared it the word of the year for 2013.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…It is characterized by a broad sense of self-worth or sufficiency as a person, as well as generalized emotions of selfacceptance, goodness, and self-reporting (Coopersmith, 1967;Crocker &Major, 1989;Rosenberg, 1965). Positive comments received on social media may help in boosting one's self-esteem (Richa et al, 2021). On the other side, a lack of positive feedback (likes, comments, etc.)…”
Section: Self-esteem and Narcissismmentioning
confidence: 99%
See 2 more Smart Citations
“…Selfies are defined as self-portraits that visually communicate (Hess, 2015) and represent an individual's (Jackson, 2019;Qiu et al, 2015) thoughts, beliefs, and creativity (Karwowski and Brzeski, 2017), and it has arisen as a culture fixated with itself (Hess, 2015). Empirical findings have indicated that selfies improve confidence and establish relationships (Barker and Rodriguez, 2019;Barry et al, 2017;Richa et al, 2021), online presence, and positive self-image. By so, the popularity of selfies has extended for a multitude of reasons as it transforms into an agent that reflects new trends in self-portrait behaviours, stretching from selfie participation through Wefies, Groufie, Ussie, Welfie, or Youie, digital manipulations focussing on editing, face tune and filters (Salomon and Brown, 2020) and various gestures, landmarks, and locations (Qiu et al, 2015).…”
mentioning
confidence: 99%